(untitled) (American Journal of Islam and Society, 2002)
On April 6-7, 2002, the Center for the Study of Islam and Democracy (CSID) held its Third Annual Conference on the theme "Democratization and Political Violence in Muslim Societies" just outside Washington, DC, at the Sheraton Crystal City Hotel in Arlington, Virginia. The conference was cosponsored by the Institute for Global Cultural Studies, State University of New York, Binghamton, NY, and the International Institute of Islamic Thought (IIIT), VA. The conference got off to a lively start on Saturday morning with Panel One: "Islam and Political Participation: Ideals, Actors, and Processes" which was chaired by Charles Butterworth of the University of Maryland, College Park. Asma Afsaruddin of the University of Notre Dame, IN, explored links between early Islamic discourse of the Khulafa ’a/-Rashidun era and modern Islamic conceptions of leadership in "Medieval Islamic Discourse on Legitimate Leadership and its Modern Implications." Wanda Kruse of the University of Guelph, Canada, discussed the underestimated role played by non-governmental political actors in the Middle East in "Civil Society in the Democratization Process: A Case Study on Cairo Islamic Women’s Organizations." Imad-ad-Dean Ahmad of the Minaret of Freedom Institute, MD, focused on the cases where democratic decision-making in government enhanced law and order in early Islamic history in "The Anti-Correlation between Democracy and Political Violence in the Experience of the Khulafa’ al-Rashidun." Moataz A. Fattah of Cairo University closed the panel with an overview of empirical evidence about Muslims’ attitudes towards democracy in "The Compatibilty of Muslims’ Beliefs and Democracy: Survey Results." Panel Two which was chaired by Jamal Barzinji of the International Institute of Islamic Thought had as its theme "Western Democracies and Authoritarian Muslim Regimes: Understanding the Relationship." Auwalu Hamisu Yadudu of Bayero University in no, Nigeria, analyzed the Shari’a ...